-4+11x=-7(-4x-11)+10x

Simple and best practice solution for -4+11x=-7(-4x-11)+10x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4+11x=-7(-4x-11)+10x equation:


Simplifying
-4 + 11x = -7(-4x + -11) + 10x

Reorder the terms:
-4 + 11x = -7(-11 + -4x) + 10x
-4 + 11x = (-11 * -7 + -4x * -7) + 10x
-4 + 11x = (77 + 28x) + 10x

Combine like terms: 28x + 10x = 38x
-4 + 11x = 77 + 38x

Solving
-4 + 11x = 77 + 38x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-38x' to each side of the equation.
-4 + 11x + -38x = 77 + 38x + -38x

Combine like terms: 11x + -38x = -27x
-4 + -27x = 77 + 38x + -38x

Combine like terms: 38x + -38x = 0
-4 + -27x = 77 + 0
-4 + -27x = 77

Add '4' to each side of the equation.
-4 + 4 + -27x = 77 + 4

Combine like terms: -4 + 4 = 0
0 + -27x = 77 + 4
-27x = 77 + 4

Combine like terms: 77 + 4 = 81
-27x = 81

Divide each side by '-27'.
x = -3

Simplifying
x = -3

See similar equations:

| 8m-4m=17+9m+3-7m | | x+3+6=-23+5x | | 3(-6-3n)+5n=-2(-8n-1) | | -6x-7x=3x-4x | | (3x-9z)2= | | -6x-7x=3x-4c | | -4+3b+b=-3+3b | | -t^2+16t+40=0 | | (3+2a)(2a-3)= | | -12-3n=6(12n-2) | | 17+11v=8+4(-7+12v) | | -3+4r=-23-r | | 0=16t-t^2+40 | | 3x-12x=10-4x | | 4=100y^2 | | -3(1+n)+7n=5(2+n) | | 12+7-6x-7=4-7x | | 0=16-t^2+40 | | 5x-5x-1=2x+5 | | 33-3a=6(a-5) | | 8(7r-1)=-8+2r | | 8(-8+4x)=-36+4x | | 8(-8+4x)=36+4x | | 2(4-4n)=-6+6n | | 9x+13=11x | | 17x+108=y | | 8w-11=69 | | 16=-16x^2+36 | | 10=-16x^2+46 | | x/(1-x)=1.44 | | F(x)=x^100-1 | | 2m=11-3m |

Equations solver categories